2017
DOI: 10.3390/molecules22091490
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antidepressant Activity Profile of Some Novel Benzothiazole Derivatives

Abstract: Within the scope of our new antidepressant drug development efforts, in this study, we synthesized eight novel benzothiazole derivatives 3a–3h. The chemical structures of the synthesized compounds were elucidated by spectroscopic methods. Test compounds were administered orally at a dose of 40 mg/kg to mice 24, 5 and 1 h before performing tail suspension, modified forced swimming, and activity cage tests. The obtained results showed that compounds 3c, 3d, 3f–3h reduced the immobility time of mice as assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Mice were located individually in a device for 4 min and interruptions of light beams to the photocells throughout horizontal and vertical behavior of the mouse were recorded by the apparatus. After each trial, the floor of the cage was cleaned with alcohol [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mice were located individually in a device for 4 min and interruptions of light beams to the photocells throughout horizontal and vertical behavior of the mouse were recorded by the apparatus. After each trial, the floor of the cage was cleaned with alcohol [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Choi and coauthors [186] employed trityl-resin as solid support for the synthesis of a diverse array of benzothiazole derivatives (19). 2-Aminobenzothiazole (18) was immobilized on the resin followed by treatment with acid chloride derivative (21) to give resin-supported carbamic chloride (22). The resinsupported carbamic chloride (22) undergoes intramolecular cyclization followed by cleavage with the TFA to give the target compound (19) (Scheme 5).…”
Section: Resin-supported Synthesismentioning
confidence: 99%
“…Ravi Kumar et al [209] have reported silica-supported sodium hydrogen sulfate as a heterogeneous catalyst for the synthesis of 2-substituted benzothiazoles (19). The desired synthesis was achieved by stirring a mixture of 2-aminothiophenol ( 18) and acid chloride derivatives (21) in the presence of the catalyst, NaHSO 4 -SiO 2 (25 % wt) under solvent-free conditions at 100°C for 12 h (Scheme 26). The scope of the developed protocol was expanded on the synthesis of 2-substituted benzoxazoles and benzimidazole derivatives.…”
Section: Silica-supported Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzothiazole derivatives display a wide spectrum of pharmacologic effects, including anti-inflammatory [4], antibacterial [5], antiviral [6], antioxidant [7], and immunomodulatory properties [8]. In addition to the central nervous system (CNS)-related pharmacologic effects, benzothiazole compounds have been reported to display selective inhibitory effects against monoamine oxidase [9,10,11,12], as well as anti-Alzheimer’s disease [13] and convulsions [14]. The antidepressant effect of a series of benzothiazole derivatives has been demonstrated through animal models such as the tail suspension test (TST) and forced swimming test (FST) [15,16].…”
Section: Introductionmentioning
confidence: 99%